APLIKASI BELAJAR ONLINE BERBASIS WEB SEBAGAI OPTIMALISASI PEMBELAJARAN UNTUK SISWA SMK - Pedja; Adi Rahman; Fahrul Kurniawan (Jurnal Pendidikan Teknologi Informatika dan Sains, 2020)
Now there is a lively online learning application in Indonesia and more and more people are taking the initiative in making online-based learning media with interesting and creative features. However, no one has specifically developed a specific online learning application for students in vocational high schools. Their existence seems to be marginalized due to the community paradigm which assumes that vocational school children do not need alternative tutoring apart from teachers at school. Though they also need the same thing with high school students and others. Based on this analysis, researchers wanted to create a web-based online learning application for vocational students. Dongkrak Prestasi is an online learning application based on learning management system that allows students to learn through video delivered by tutors. This research uses the waterfall method. Based on the test results, this learning application is already running with the results of testing the user interface 98%, the basic functions of the system 100%, and 100% validation. In conclusion, this application runs very well.